The Algorithmic Fiqh: Qiyas and the Cryptocurrency Paradigm - Fatima Zohra Benali; Wildan Miftahussurur Miftahussurur; Rijal Ali Santos Santos; Zaenol Hasan (Postgraduate Programme of UIN Kiai Haji Achmad Siddiq Jember, 2025)
This study examines the application of qiyas (analogical reasoning) in assessing the legality of cryptocurrency within Islamic law, particularly through the fatwas issued by the National Sharia Council of the Indonesian Ulema Council (DSN-MUI). As cryptocurrency emerges as a significant innovation in the economic sector, the research analyzes classical fiqh texts and draws analogies with paper money to identify essential criteria for cryptocurrency to be considered a legitimate medium of exchange, including being valuable, pure, transferable, and beneficial. The findings indicate that while cryptocurrency lacks official backing, its value is derived from societal trust in blockchain technology. The study emphasizes the necessity for cryptocurrency transactions to comply with Sharia principles, avoiding elements of riba, gharar, and maysir. Additionally, it highlights the importance of collaboration among scholars, academics, and practitioners in Sharia economics to develop responsive fatwas and policies that address technological advancements and societal needs. Furthermore, to provide a broader perspective, examples from other countries, such as Malaysia, Algeria, and Morocco, can be referenced to understand how different Islamic authorities approach the regulation and assessment of cryptocurrency. For instance, Malaysia's Shariah Advisory Council has recognized cryptocurrencies under certain conditions, while Algeria has outright banned their use due to concerns over their volatility and speculative nature. Morocco, on the other hand, has issued warnings about the risks associated with cryptocurrency, despite the growing global interest in digital currencies. By examining these diverse approaches, the research can offer a more comprehensive understanding of how cryptocurrency fits within the frameworks of Islamic finance and law across different contexts. This research contributes to the discourse on integrating modern financial systems with Islamic principles, suggesting that cryptocurrencies can be utilized within Islamic economies if they adhere to Sharia guidelines. Ultimately, the study aims to provide practical guidance for Muslims in conducting economic activities in the digital era while leveraging technological progress to enhance welfare and prosperity.